Reflektif Teologi Digital di Era Pasca Pandemi dan Post-Truth:: Strategi Edukasi Iman dan Kritik terhadap Kultur Digital - Arifianto, Yonatan Alex; Sumual, Elisa Nimbo; Rahayu, Yohana Fajar (STT Bala Keselamatan Palu, 2025)
Abstract: The rapid development of digital technology, especially in the wake of the Covid-19 pandemic, has prompted churches and theological institutions to adapt their ministry and faith education to the digital space. However, this transformation brings not only opportunities but also serious challenges, particularly in terms of spiritual shallowness, stagnation of faith communities, and the emergence of instant religious consumption models. Concurrently, the post-truth era has given rise to an epistemological crisis, where subjective feelings, relativism, and personal or communal opinions are trusted more than objective truth, including in matters of faith. The flood of hoax content, theological disinformation, and the influence of digital platforms on faith understanding have become key concerns in the dynamics of digital religious life. This study aims to theologically examine the expansion of digital theology in responding to this crisis through strategies of faith education and criticism of digital culture. Using a descriptive qualitative method based on literature review, It can be concluded that the understanding of digital theology as a contextual response in the post-pandemic era is presented as digital faith education within the paradigm shift in theological learning. Despite the post-truth crisis and theological challenges, this serves as a pathway for theological criticism of digital culture to build faith education and digital spirituality. Thus, the church is challenged to be present as light and salt in the digital space as an agent of truth and restoration. Abstrak: Perkembangan teknologi digital yang pesat, terutama pasca-pandemi Covid-19, telah mendorong gereja dan institusi teologi untuk mengadaptasi pelayanan dan pendidikan iman ke dalam ruang digital. Namun, transformasi ini tidak hanya membawa peluang, tetapi juga tantangan serius, terutama dalam hal pendangkalan spiritualitas, stagnasi komunitas iman, dan munculnya model konsumsi religius yang instan. Bersamaan dengan itu, era post-truth telah melahirkan krisis epistemologis, di mana nilai perasaan subjektif dan relaitiv serta opini persoanal maupun komunal lebih dipercaya daripada kebenaran objektif, termasuk dalam perkara iman. Fenomena membanjirnya konten hoaks, disinformasi teologis, dan pengaruh Flatform digtital terhadap pemahaman iman menjadi perhatian utama dalam dinamika kehidupan beragama digital. Penelitian ini bertujuan untuk mengkaji secara teologis ekspansi teologi digital dalam merespons krisis tersebut melalui strategi edukasi iman dan kritik terhadap kultur digital. Menggunakan metode kualitatif deskriptif berbasis studi pustaka,. Maka dapat disimpulkan bahwa pemahaman akan teologi digital sebagai respons kontekstual di era pasca-pandemi, dihadirkan sebagai pendidikan iman digital dalam perubahan paradigma pembelajaran teologis. walaupun adanya krisis post-truth dan tantangan teologis menjadi jalan bagi kritik teologis terhadap kultur digital membangun edukasi iman dan spiritualitas digital. Dengan demikian, gereja ditantang untuk hadir secara nyata dalam terang dan garam di ruang digital sebagai agen kebenaran dan pemulihan.